Spain : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2001 Article IV Consultation highlights that the economy of Spain grew by more than 4 percent annually during 1997-2000-reflecting strong consumption, competitive exports, wage moderation, and supply conditions enhanced by structural reforms. Annualized real GDP growth was about 2 percent in the third quarter of 2001, compared with 2.5 percent and 3 percent, respectively, in the second and first quarters. Industrial production has been decreasing during most of 2001, and in November stood about 1 percent lower than a year before.